Factors Associated With HIV Testing Among Men in Haiti: Results From the 2012 Demographic and Health Survey - Donaldson F. Conserve PhD (American Journal of Men's Health, 2017)
HIV testing serves as the gateway to HIV prevention and treatment. However, research examining men’s HIV testing behaviors in the Caribbean remains limited. The Andersen Behavioral Model of Health Services Utilization was used to examine factors associated with HIV testing among 7,354 men who participated in the 2012 Demographic and Health Survey conducted in Haiti. Few men (35%) reported having ever been tested for HIV. Logistic regression analyses revealed that HIV testing increased with education and wealth. Marital status was associated with HIV testing, with married men more likely to have been tested (adjusted odds ratio: 2.57, 95% CI [2.07, 3.19]) than unmarried men. Positive attitudes toward people living with HIV, indicated by willing to care for a relative who has HIV/AIDS, was also correlated with higher odds of having been tested (adjusted odds ratio: 1.28, 95% CI [1.08, 1.51]). Men who reported condom use during last sex were more likely to have been tested (odds ratio: 1.58, 95% CI [1.33, 1.88). The findings indicate that HIV testing rates remain low among men in Haiti and more efforts are needed to increase HIV testing among men who are not married, have low level of education, and engage in unprotected sex.